Estudo da relação da anexina A1 com proteínas de reparo, p53 e fatores clínico-laboratoriais em pacientes com câncer colorretal - Ydy, Lenuce Ribeiro Aziz (2015)
The colorectal cancer is one of most frequent neoplasia in adult population, inBrazil thiscancer is the third in incidence in man and the fourth in woman. The increasing advancementin molecular biology research have contributes for understanding the biological behaviorandsome biological markers. The annexin A1 protein (ANXA1) is related with sometypesoftumor and its study in colorectal cancer in scientific literature is been done, but discreetlyyet.The goal of this study was correlate the expression of the proteins annexin A1, p53, DNA-mismatch repair protein MLH1, MSH2 and MSH6 with clinical aspects and histopathologyaspects in patients with colorectal cancer. Annexin-A1 has been implicated in varioustumortypes, but few studies have investigated its involvement in colorectal cancer. The studyaimedto analyze ANXA1 expression in the normal and colorectal tumor tissues of 104 patientswhounderwent surgery for CRC and to correlate ANXA1 expression with predictiveclinicpathological variables. Hematoxylin-eosin and immunohistochemical staining wereusedforthe analysis. ANXA1 expression was higher in colorectal cancer than in normal margintissue(p=0,0001). However, no differences were observed when we analyzed the ANXA1expression in colon and rectal tumors (p=0,830). Also, this protein positivity was associatedwith increased carcinoembryonic antigen levels (p=0,004). Our data in the DNA-mismatchrepair proteins expression was in accordance to the literature. And their positivitywasnotassociated with ANXA1 presence in colorectal cancer. The high incidence of ANXA1positive expression in colorectal cancer and its association with carcinoembryonicantigenlevels might indicate the importance of this protein in the colorectal cancer biology.